Colleen Lanz

Due September 1, 2011
HW #2
1. (a) Find the Lagrangian and Lagrange’s equations of motion for the simple pendulum. Use θ as the
generalized coordinate.
Solution.
First,
T =
1
2
m( ˙ x
2
+ ˙ y
2
)
U = −mgy
L = T −U =
1
2
m( ˙ x
2
+ ˙ y
2
) + mgy
Note, to transfer this into θ as the generalized coordinate:
x = l sin θ =⇒ ˙ x =
˙
θl cos θ
x = l cos θ =⇒ ˙ x = −
˙
θl sin θ
So
L =
1
2
m(
˙
θl)
2
+ mgl cos θ
And
∂L
∂θ
=
d
dt
_
∂L

˙
θ
_
−mgl sin θ = m
¨
θl
2

g
l
sin θ =
¨
θ
1
(b) Use x as a generalized coordinate.
Solution. Note that
l
2
= x
2
+ y
2
=⇒ y =
_
l
2
−x
2
=⇒ ˙ y =
(x ˙ x)
2
l
2
−x
2
Thus,
L =
1
2
m( ˙ x
2
+ ˙ y
2
) + mgy
=
1
2
m
_
˙ x
2
+
(x ˙ x)
2
l
2
−x
2
_
+ mg
_
l
2
−x
2
=
1
2
m˙ x
2
_
1 +
x
2
l
2
−x
2
_
+ mg
_
l
2
−x
2
Then, solving each side of Lagrange’s equation independently,
∂L
∂x
= −
2m˙ x
2
xl
2
(l
2
−x
2
)
2
+
mgx

l
2
−x
2
∂L
∂ ˙ x
= m˙ x
_
1 +
x
2
l
2
−x
2
_
d
dt
∂L
∂ ˙ x
= m˙ x
_
2x ˙ xl
2
(l
2
−x
2
)
2
_
+ m¨ x
_
1 +
x
2
l
2
−x
2
_
Thus, equating both sides, and multiplying by
(l
2
−x
2
)
2
m
, we get
−2 ˙ x
2
xl
2
+ gx(l
2
−x
2
)
3
2
= 2x ˙ xl
2
+ ¨ xl
2
(l
2
−x
2
)
4 ˙ x
2
xl
2
+ gx(l
2
−x
2
)
3
2
l
2
(l
2
−x
2
)
= ¨ x
2
2. Two points of mass m are joined by a rigid weightless rod of length l. The center of the rod is constrained
to move in a vertical circle of radius R.
(a) How many degrees of freedom?
Solution.
The first degree of freedom is the position of the center of the rod on the circular track and the second
is the angle θ
m
that the rod makes with the horizon so there are two degrees of freedom in total.
3
(b) Find the Lagrangian.
Solution. First, we recognize that the position of the center of the rod (cor) is
x
cor
= Rcos θ
r
y
cor
= Rsin θ
r
Now, find the position of the mass in relation to the center of the rod:
x
1
= x
cor
+
l
2
cos θ
m
= Rcos θ
r
+
l
2
cos θ
m
x
2
= x
cor

l
2
cos θ
m
= Rcos θ
r

l
2
cos θ
m
y
1
= y
cor
+
l
2
sin θ
m
= Rsin θ
r
+
l
2
sin θ
m
y
2
= y
cor

l
2
sin θ
m
= Rsin θ
r

l
2
sin θ
m
Hence,
L =
1
2
m( ˙ x
2
1
+ ˙ y
2
1
+ ˙ x
2
2
+ ˙ y
2
2
) −mg(y
1
+ y
2
).
Note that
˙ x
1
= −
˙
θ
r
Rsin θ
r

l
2
˙
θ
m
sin θ
m
˙ x
2
= −
˙
θ
r
Rsin θ
r
+
l
2
˙
θ
m
sin θ
m
˙ y
1
= −
˙
θ
r
Rcos θ
r
+
l
2
˙
θ
m
cos θ
m
˙ y
2
= −
˙
θ
r
Rcos θ
r

l
2
˙
θ
m
cos θ
m
From this, we obtain that
˙ x
2
1
+ ˙ y
2
1
=
˙
θ
2
r
R
2
+
l
2
4
˙
θ
2
m
+ l
˙
θ
r
˙
θ
m
cos(θ
r
+ θ
m
)
˙ x
2
2
+ ˙ y
2
2
=
˙
θ
2
r
R
2
+
l
2
4
˙
θ
2
m
−l
˙
θ
r
˙
θ
m
cos(θ
r
+ θ
m
)
and
U = mg(y
1
+ y
2
) = mg2Rsin θ
r
.
Hence,
L =
1
2
m(2
˙
θ
2
r
R
2
+
l
2
2
˙
θ
2
m
) −2mgRsin θ
r
= m(
˙
θ
2
r
R
2
+
l
2
4
˙
θ
2
m
−2gRsin θ
r
)
4
(c) What are the constants of motion?
Solution. First, we note that since θ
m
does not appear explicitly in L, it is cyclic and hence a constant
of motion. The total mechanical energy is also a constant of motion because L does not explictly depend
on t and so
dE
dt
= 0.
(d) Find the equations of motion.
Solution. For θ
r
, we have
∂L
∂θ
r
=
d
dt
_
∂L

˙
θ
r
_
−2gmRcos θ
r
= 2m
¨
θ
r
R
2

g
R
cos θ
r
=
¨
θ
r
(1)
and for θ
m
,
∂L
∂θ
m
=
d
dt
_
∂L

˙
θ
m
_
0 =
l
2
2
¨
θ
m
0 =
¨
θ
m
.
(e) Find the solutions around the equilibrium points of the system.
Solution. At equilibrium,
¨
θ
r
= 0 and
¨
θ
m
= 0 but we’ve seen that
¨
θ
m
= 0∀t so this is non-exclusionary.
FOr
¨
θ
r
= 0, we see that (1) implies
g
R
cos θ
r
= 0 =⇒ θ
r
=
π
2
+ nπ for n ∈ Z.
So θ
0r
= {
π
2
+ nπ} = {
π
2
,

2
}. (All of the other n ∈ Z are physically represented by the two above.
Now, for small, (1) implies
¨
θ
r
= −
g
R
cos(
˜
θ
1
)
= −
g
R
cos(θ
0r
+ )
= −
g
R
(cos(θ
0r
cos() −sin(θ
0
) sin())

g
R
.
Hence, near θ
0r
= {
π
2
,

2
},
θ
r
(t) = Acos
__
g
R
t
_
+ B sin
__
g
R
t
_
.
5
3. A particle moves in a central potential:
Φ(r) = αr
2
.
(a) Find the Lagrangian in terms of polar coordinates.
First, we recall that
T =
1
2
m( ˙ x
2
+ ˙ y
2
+ ˙ z
2
)
U = αr
2
where
x = r sin θ cos φ
y = r sin θ sin φ
z = r cos θ
Then,
˙ x = r(−
˙
φsin θ sin φ +
˙
θ cos θ cos φ) + ˙ r sin θ cos φ
˙ y = r(
˙
φsin θ cos φ +
˙
θ cos θ sin φ) + ˙ r sin θ sin φ
˙ z = −r
˙
θ sin θ + ˙ r cos θ
Furthermore, after some simplification, we see
˙ x
2
+ ˙ y
2
+ ˙ z
2
= r
2
(
˙
φ
2
sin
2
θ +
˙
θ
2
cos
2
θ) + ˙ r
2
sin
2
θ + 2 sin(2θ)
+ r
2
˙
t
2
sin
2
θ + ˙ r
2
cos
2
θ −2 sin(2θ)
= r
2
(
˙
φ
2
sin
2
θ +
˙
θ
2
) + ˙ r
2
Hence,
L =
1
2
m(r
2
(
˙
φ
2
sin
2
θ +
˙
θ
2
) + ˙ r
2
) −αr
2
. (2)
6
(b) What are the constants of motion?
Solution. φ is one constant of motion because it does not explictly occur in L. Also, because the
Lagrangian is not explicitly time-dependent and the kinetic energy is the sum of squares, the mechanical
energy is also a constant of motion. We may find two more:
p
θ
=
∂L

˙
θ
= mr
2
˙
θ
p
φ
=
∂L

˙
φ
= mr
2
˙
φsin
2
θ
(c) Assuming motion was initially in the x −y plane, find an equation of motion for r.
Solution. Motion in the x −y plane means that θ =
π
2
. (2) gives us
L =
1
2
m(r
2
(
˙
φ
2
+
˙
θ
2
) + ˙ r
2
) −αr
2
and the equations of motion for r are given by:
∂L
∂r
=
d
dt
∂L
∂ ˙ r
mr(
˙
φ
2
+
˙
θ
2
) −
2αr
m
= m¨ r
r
_
˙
φ
2


m
_
= ¨ r
Then, using the fact that
˙
φ =
p
φ
mr
2
sin
2
θ
,
we get that
¨ r = r
_
_
p
φ
mr
2
sin
2
θ
_
2


m
_
. (3)
7
(d) Find an equation of motion for u =
1
r
2
.
Solution. Note that if u = r
−2
then r
2
=
1
u
and
r = u

1
2
˙ r = −
1
2
u

3
2
˙ u
¨ r = −
1
2
_

3
2
u

5
2
( ˙ u)
2
+ u

3
2
¨ u
_
=
3
4
u

5
2
_
( ˙ u)
2

2
3
u¨ u
_
˙ u =
du


dt
=
du

p
φ
mr
2
sin
2
θ
¨ u =
d
dt
_
du

_
_
p
φ
mr
2
sin
2
θ
_
Then (3) implies that
¨ r = r
_
_
p
φ
mr
2
_
2


m
_
3
4
( ˙ u
2

2
3
u¨ u) = u
2
_
_
p
φ
mr
2
_
2


m
_
. ¸¸ .
:=M
3
4M
_
_
du

p
φ
mr
2
sin
2
θ
_
2

2
3
u
d
dt
du

p
φ
mr
2
sin
2
θ
_
= u
2
and if we can assume that the motion is in the x −y plane, then θ = π/2 and so
_
3
4M
_
du

p
φ
mr
2
_
= u(φ)
du

=
_
M
3
2p
φ
mr
2
. ¸¸ .
:=C
u(φ)
u(φ) = Ae
φC
8
(e) Solve for u(θ).
Solution. Assuming θ =
π
2
, so that
˙
θ = 0, we have
¨ u = −2u
˙
φ
2
+
3
2
˙ u
2
u
+ 4
α
m
u.
We must get rid of φ in (4):
∂L
∂φ
=
d
dt
∂L

˙
φ
0 = mu
−1
¨
φ
0 =
¨
φ
φ(t) = c
1
t + c
2
.
Hence (7) becomes
¨ u = −2uc
2
1
+
3
2
˙ u
2
u
+ 4
α
m
u
= 2u(2
α
m
−c
2
1
) +
3
2
˙ u
2
u
=⇒ u(t) = k
2
sec
2
(
_
2
α
m

˙
φ
2
(t + 2k
1
))
9
(f) For which α and initial conditions is the motion a closed orbit?
Solution. We would like to find the conditions under which u →∞ (i.e., r converges): So, replacing r
with u, (2) becomes
L =
1
2
m
_
1
u
(
˙
φ
2
sin
2
θ +
˙
θ
2
) +
˙ u
2
4u
3
_

α
u
(4)
Now,
∂L
∂u
=
1
2
m(−u
−2
(
˙
φ
2
sin
2
θ +
˙
θ
2
) −
3
4
u
−4
˙ u
2
) + αu
−2
(5)
∂L
∂ ˙ u
=
1
4
mu
−3
˙ u
d
dt
∂L
∂ ˙ u
=
1
4
m(u
−3
¨ u −3u
−4
˙ u
2
) (6)
Equating (5) and (6), then multiplying both sides by
4u
m
:
u
−2
_
1
2
m(−(
˙
φ
2
sin
2
θ +
˙
θ
2
) −
3
4
u
−2
˙ u
2
) + α
_
=
1
4
mu
−2
_
u
−1
¨ u −3u
−2
˙ u
2
_
−2u(
˙
φ
2
sin
2
θ +
˙
θ
2
) +
3
2
˙ u
2
u
+ 4
α
m
u = ¨ u (7)
Assuming θ =
π
2
, so that
˙
θ = 0, we have
¨ u = −2u
˙
φ
2
+
3
2
˙ u
2
u
+ 4
α
m
u.
We must get rid of φ in (4):
∂L
∂φ
=
d
dt
∂L

˙
φ
0 = mu
−1
¨
φ
0 =
¨
φ
φ(t) = c
1
t + c
2
.
Hence (7) becomes
¨ u = −2uc
2
1
+
3
2
˙ u
2
u
+ 4
α
m
u
= 2u(2
α
m
−c
2
1
) +
3
2
˙ u
2
u
=⇒ u(t) = k
2
sec
2
(
_
2
α
m

˙
φ
2
(t + 2k
1
))
Finally,
0 = cos(
_
2
α
m

˙
φ
2
(t + 2k
1
))
π
2
+ nπ =
_
2
α
m

˙
φ
2
(t + 2k
1
)
α =
m
2
_
_
π
2
+ nπ
2k
1
_
2
+
˙
φ
2
_
10
4. Consider a system consisting of two rods and one particle, all of mass m. They move in the x − y plane
without external potential. Rods have length l and the springs have equilibrium length l. The pivot points
of the rods are seperated by a distance 4l.
11

Note that l 2 = x2 + y 2 =⇒ =⇒ Thus. m 3 y= y= ˙ l 2 − x2 (xx)2 ˙ l 2 − x2 we get −2x2 xl2 + gx(l2 − x2 ) 2 = 2xxl2 + xl2 (l2 − x2 ) ˙ ˙ ¨ 4x2 xl2 + gx(l2 − x2 ) 2 ˙ =x ¨ l2 (l2 − x2 ) 3 2 .(b) Use x as a generalized coordinate. Solution. 1 L = m(x2 + y 2 ) + mgy ˙ ˙ 2 1 (xx)2 ˙ + mg l2 − x2 = m x2 + 2 ˙ 2 l − x2 x2 1 + mg l2 − x2 = mx2 1 + 2 ˙ 2 l − x2 Then. ∂L 2mx2 xl2 ˙ mgx =− 2 +√ 2 )2 ∂x (l − x l 2 − x2 2 ∂L x = mx 1 + 2 ˙ ∂x ˙ l − x2 d ∂L 2xxl2 ˙ x2 = mx ˙ + m¨ 1 + 2 x dt ∂ x ˙ (l2 − x2 )2 l − x2 Thus. equating both sides. solving each side of Lagrange’s equation independently. and multiplying by (l2 −x2 )2 .

The center of the rod is constrained to move in a vertical circle of radius R.2. Two points of mass m are joined by a rigid weightless rod of length l. 3 . The first degree of freedom is the position of the center of the rod on the circular track and the second is the angle θm that the rod makes with the horizon so there are two degrees of freedom in total. (a) How many degrees of freedom? Solution.

1 l2 ˙ 2 ˙2 L = m(2θr R2 + θm ) − 2mgR sin θr 2 2 l2 ˙ 2 ˙2 = m(θr R2 + θm − 2gR sin θr ) 4 and 4 . ˙ 1 ˙2 ˙ 2 ˙2 2 Note that l ˙ ˙ x1 = −θr R sin θr − θm sin θm ˙ 2 l ˙ ˙ x2 = −θr R sin θr + θm sin θm ˙ 2 l ˙ ˙ y1 = −θr R cos θr + θm cos θm ˙ 2 l ˙ ˙ y2 = −θr R cos θr − θm cos θm ˙ 2 From this. Solution.(b) Find the Lagrangian. Hence. find the position of the mass in relation to the center of the rod: x1 = xcor + l l cos θm = R cos θr + cos θm 2 2 l l x2 = xcor − cos θm = R cos θr − cos θm 2 2 l l y1 = ycor + sin θm = R sin θr + sin θm 2 2 l l y2 = ycor − sin θm = R sin θr − sin θm 2 2 Hence. we recognize that the position of the center of the rod (cor) is xcor = R cos θr ycor = R sin θr Now. 1 L = m(x2 + y1 + x2 + y2 ) − mg(y1 + y2 ). First. we obtain that ˙2 x2 + y1 = θr R2 + ˙ 1 ˙2 l2 ˙ 2 ˙ ˙ θ + lθr θm cos(θr + θm ) 4 m l2 ˙ 2 ˙ ˙ ˙2 x2 + y2 = θr R2 + θm − lθr θm cos(θr + θm ) ˙ 2 ˙2 4 U = mg(y1 + y2 ) = mg2R sin θr .

(c) What are the constants of motion? Solution. ¨ FOr θr = 0. dt (d) Find the equations of motion. we have d ∂L = ∂θr dt ∂L ˙ ∂ θr (1) ¨ −2gmR cos θr = 2mθr R2 g ¨ − cos θr = θr R and for θm . 3π }. d ∂L ∂L = ˙ ∂θm dt ∂ θm l2 ¨ 0 = θm 2 ¨m . for small. R Hence. near θ0r = { π . θr = 0 and θm = 0 but we’ve seen that θm = 0∀t so this is non-exclusionary. So θ0r = { π + nπ} = { π . we see that (1) implies g cos θr = 0 R =⇒ θr = π + nπ 2 for n ∈ Z. ¨ ¨ ¨ Solution. we note that since θm does not appear explicitly in L. First. (All of the other n ∈ Z are physically represented by the two above. 2 2 θr (t) = A cos g t + B sin R g t . 3π }. The total mechanical energy is also a constant of motion because L does not explictly depend on t and so dE = 0. For θr . At equilibrium. 2 2 2 Now. Solution. (1) implies g ¨ ˜ θr = − cos(θ1 ) R g = − cos(θ0r + ) R g = − (cos(θ0r cos( ) − sin(θ0 ) sin( )) R g ≈ . it is cyclic and hence a constant of motion. 0=θ (e) Find the solutions around the equilibrium points of the system. R 5 .

after some simplification. we recall that 1 ˙ ˙ ˙ T = m(x2 + y 2 + z 2 ) 2 U = αr2 where x = r sin θ cos φ y = r sin θ sin φ z = r cos θ Then. 1 ˙ ˙ L = m(r2 (φ2 sin2 θ + θ2 ) + r2 ) − αr2 .3. (a) Find the Lagrangian in terms of polar coordinates. ˙ ˙ x = r(−φ sin θ sin φ + θ cos θ cos φ) + r sin θ cos φ ˙ ˙ ˙ ˙ y = r(φ sin θ cos φ + θ cos θ sin φ) + r sin θ sin φ ˙ ˙ ˙ z = −rθ sin θ + r cos θ ˙ ˙ Furthermore. we see ˙ ˙ x2 + y 2 + z 2 = r2 (φ2 sin2 θ + θ2 cos2 θ) + r2 sin2 θ + 2 sin(2θ) ˙ ˙ ˙ ˙ 2 ˙2 2 2 2 + r t sin θ + r cos θ − 2 sin(2θ) ˙ ˙ ˙ = r2 (φ2 sin2 θ + θ2 ) + r2 ˙ Hence. ˙ 2 (2) 6 . A particle moves in a central potential: Φ(r) = αr2 . First.

Also.(b) What are the constants of motion? Solution. (3) 7 . 2 sin2 θ mr − 2α m . Solution. (2) gives us 2 1 ˙ ˙ ˙ L = m(r2 (φ2 + θ2 ) + r2 ) − αr2 2 and the equations of motion for r are given by: ∂L d ∂L = ∂r dt ∂ r ˙ 2αr ˙ ˙ mr(φ2 + θ2 ) − = m¨ r m 2α ˙ r φ2 − =r ¨ m Then. because the Lagrangian is not explicitly time-dependent and the kinetic energy is the sum of squares. using the fact that ˙ φ= we get that r=r ¨ pφ 2 sin2 θ mr 2 pφ . Motion in the x − y plane means that θ = π . We may find two more: ∂L ˙ = mr2 θ ˙ ∂θ ∂L ˙ pφ = = mr2 φ sin2 θ ˙ ∂φ pθ = (c) Assuming motion was initially in the x − y plane. φ is one constant of motion because it does not explictly occur in L. the mechanical energy is also a constant of motion. find an equation of motion for r.

then θ = π/2 and so 3 4M du pφ dφ mr2 = u(φ) M 2pφ u(φ) 3 mr2 :=C φC du = dφ u(φ) = Ae 8 .(d) Find an equation of motion for u = r12 . Note that if u = r−2 then r2 = 1 u 1 and r = u− 2 1 3 ˙ r = − u− 2 u ˙ 2 3 1 3 5 r=− ¨ − u− 2 (u)2 + u− 2 u ˙ ¨ 2 2 2 3 5 ˙ = u− 2 (u)2 − u¨ u 4 3 du dφ u= ˙ dφ dt pφ du = dφ mr2 sin2 θ pφ d du u= ¨ 2 sin2 θ dt dφ mr Then (3) implies that r=r ¨ 3 2 2 (u − u¨) = u2 ˙ u 4 3 3 4M pφ du 2 sin2 θ dφ mr 2 pφ 2 2α − mr2 m 2 pφ 2α − 2 mr m :=M pφ 2 d du − u 2 sin2 θ 3 dt dφ mr = u2 and if we can assume that the motion is in the x − y plane. Solution.

Assuming θ = π . ˙ Solution. 2 u m =⇒ 9 . we have 2 ˙ u = −2uφ2 + ¨ We must get rid of φ in (4): d ∂L ∂L = ˙ ∂φ dt ∂ φ ¨ 0 = mu−1 φ ¨ 0=φ φ(t) = c1 t + c2 . so that θ = 0. Hence (7) becomes ˙ α 3 u2 +4 u 2 u m α 3 u2 ˙ = 2u(2 − c2 ) + 1 m 2 u α ˙ u(t) = k2 sec2 ( 2 − φ2 (t + 2k1 )) m u = −2uc2 + ¨ 1 ˙ 3 u2 α + 4 u.(e) Solve for u(θ).

u = −2uφ2 + ¨ 2 u m We must get rid of φ in (4): ∂L d ∂L = ˙ ∂φ dt ∂ φ ¨ 0 = mu−1 φ ¨ 0=φ φ(t) = c1 t + c2 . replacing r with u. 0 = cos( 2 π + nπ = 2 α= m 2 2 α ˙ − φ2 (t + 2k1 )) m α ˙ − φ2 (t + 2k1 ) m π 2 + nπ 2k1 2 ˙ + φ2 10 . r converges): So. We would like to find the conditions under which u → ∞ (i..(f) For which α and initial conditions is the motion a closed orbit? Solution. we have 2 ˙ α 3 u2 ˙ + 4 u. then multiplying both sides by u−2 4u m: (5) (6) 1 3 1 ˙ ˙ m(−(φ2 sin2 θ + θ2 ) − u−2 u2 ) + α = mu−2 u−1 u − 3u−2 u2 ˙ ¨ ˙ 2 4 4 ˙ α 3 u2 ˙ ˙ +4 u=u ¨ −2u(φ2 sin2 θ + θ2 ) + 2 u m ˙ Assuming θ = π .e. Hence (7) becomes 3 u2 ˙ α +4 u 2 u m 3 u2 ˙ α = 2u(2 − c2 ) + 1 m 2 u α ˙ u(t) = k2 sec2 ( 2 − φ2 (t + 2k1 )) m u = −2uc2 + ¨ 1 (7) =⇒ Finally. 1 3 ∂L ˙ ˙ = m(−u−2 (φ2 sin2 θ + θ2 ) − u−4 u2 ) + αu−2 ˙ ∂u 2 4 ∂L 1 = mu−3 u ˙ ∂u ˙ 4 d ∂L 1 = m(u−3 u − 3u−4 u2 ) ¨ ˙ dt ∂ u ˙ 4 Equating (5) and (6). (2) becomes 1 α 1 ˙2 2 u2 ˙ ˙ L= m (φ sin θ + θ2 ) + 3 − (4) 2 u 4u u Now. so that θ = 0.

4. 11 . all of mass m. The pivot points of the rods are seperated by a distance 4l. Rods have length l and the springs have equilibrium length l. Consider a system consisting of two rods and one particle. They move in the x − y plane without external potential.

Master your semester with Scribd & The New York Times

Special offer for students: Only $4.99/month.

Master your semester with Scribd & The New York Times

Cancel anytime.